If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 = 25 + 6s Solving 67 = 25 + 6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6s' to each side of the equation. 67 + -6s = 25 + 6s + -6s Combine like terms: 6s + -6s = 0 67 + -6s = 25 + 0 67 + -6s = 25 Add '-67' to each side of the equation. 67 + -67 + -6s = 25 + -67 Combine like terms: 67 + -67 = 0 0 + -6s = 25 + -67 -6s = 25 + -67 Combine like terms: 25 + -67 = -42 -6s = -42 Divide each side by '-6'. s = 7 Simplifying s = 7
| -13+a=-6 | | 15-2x-7=14 | | 2-2m=8 | | 67=256s | | -x(x^2+4)= | | 7s-10=46 | | 26=3u-64 | | E^3-2x=10 | | 2y+4=4y-6 | | 38k=2204 | | 60x-40=50x | | 6x-1+8x=3x+3-5x | | 19y=95 | | g+11=-3 | | 2x-8x+6=19 | | 363-x=-201 | | 4x=10+y | | 3(x-1)+x=4x+2 | | (2x-1)*(2x+1)= | | logpq=r | | U=233+37n | | 10x+90=20x+120 | | (3x+1/2x-3)=(6x-5/4x+7) | | -55-p= | | U=7(4n+32)+9(n+1) | | 3(4x+1)-5=2y+3x-6 | | x-(x*0.1)=1.12 | | 160+0.25x=325 | | y=x*x-8x+15 | | X-3(2X+3)=8.5X | | -4(2x-4)+3x-4=37 | | 10+73=8x+191 |